Conhecimento das mulheres Wai Wai: estudo sobre o artesanato feito em sementes de morototó - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This project aims to study body adornments in morototó seed made by Wai Wai indigenous women. Body adornments are understood as a series of objects used as bracelets, necklaces, belts, armbands, bags, among others. Currently, in addition to the morototó seed, plastic and glass beads are also used to make the ornaments, but the traditional way of making them, prior to direct and indirect contacts with Europeans and North Americans, is with the seed. The methodology used was that of interviewing women who knew this craft, in addition to participating in the activity and recording images, an approach already used in the production of other artifacts of Wai Wai material culture. To carry out this research, we went into the field in the Mapuera village and interviewed four artisans, from four Mawayana, Katwena, Wai Wai and Xerew peoples. The objective was to value and observe how this diversity of people in the Mapuera village influences knowledge about handicrafts. Wai. And from this inventory, understand the processes of change that occurred in the manufacture of these props and the reasons that led to this. We believe that the historical and current description of this handicraft is a way to preserve a traditional knowledge of Wai Wai women and that its written record can help in perpetuating this knowledge for my own people.
Keywords: Artesanato; Sementes de morototó; Povo Wai Wai; Mulheres; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS